Prescribing new drugs: qualitative study of influences on consultants and general practitioners - Jones, Miren I (BMJ, 2001)
OBJECTIVE: To explore consultants' and general practitioners' perceptions of the factors that influence their decisions to introduce new drugs into their clinical practice. DESIGN: Qualitative study using semistructured interviews. Monitoring of hospital and general practice prescribing data for eight new drugs. SETTING: Teaching hospital and nearby general hospital plus general practices in Birmingham. PARTICIPANTS: 38 consultants and 56 general practitioners who regularly referred to the teaching hospital. MAIN OUTCOME MEASURES: Reasons for prescribing a new drug; sources of information used for new drugs; extent of contact between consultants and general practitioners; and amount of study drugs used in hospitals and by general practitioners. RESULTS: Consultants usually prescribed new drugs only in their specialty, used few new drugs, and used scientific evidence to inform their decisions. General practitioners generally prescribed more new drugs and for a wider range of conditions, but their approach varied considerably both between general practitioners and between drugs for the same general practitioner. Drug company representatives were an important source of information for general practitioners. Prescribing data were consistent with statements made by respondents. CONCLUSIONS: The factors influencing the introduction of new drugs, particularly in primary care, are more multiple and complex than suggested by early theories of drug innovation. Early experience of using a new drug seems to strongly influence future use.